Morphology, systematics and palaeoecology of pachycormid fishes - Dobson, CE (2019)
Pachycormiformes are one of the earliest diverging groups of stem teleosts, and are distinguished by substantial ecomorphological disparity: from mid-sized predators, to giant suspension-feeders. Despite this, and their relatively abundant fossil record, they lack detailed study. Here, I use computed tomography scanning to re-examine and redescribe well-preserved suspension-feeding (Martillichthys) and predatory (Pachycormus) pachycormiforms. I report previously unobserved aspects of the gill skeleton (Martillichthys), neurocranium (both) and pectoral girdle (Pachycormus). I also identify features previously unreported in pachycormiforms, including a median vomer (Martillichthys: considered a teleost character but likely convergent), a urohyal (Pachycormus: considered a teleost character), and a metapterygium-like radial (Pachycormus: considered a primitive actinopterygian character). These morphological observations, along with molecular and stratigraphic data, inform phylogenetic analyses using maximum parsimony and Bayesian methods in order to resolve pachycormiform interrelationships, estimate divergence times, and test a hypothesized second origin of suspension-feeders within the group. Results corroborate previous hypotheses of pachycormiform relationships, but the inclusion of stratigraphic data results in an alternative pattern of relationships. Finally, I use quantitative biostratigraphic models, incorporating fossil record heterogeneity, to estimate credible intervals of suspension-feeding pachycormiform extinction and suspension-feeding chondrichthyan emergence. I find some chondrichthyan lineages may have appeared as early as the Early Cretaceous, and cannot reject that pachycormiforms may have persisted into the Eocene. However, the presence of other putative suspension-feeding chondrichthyans in the Cretaceous that are absent in the Cenozoic suggests modern lineages may (as hypothesized here and elsewhere) have emerged following the faunal turnover of the end Cretaceous. This thesis builds a clearer picture of pachycormiform morphology and interrelationships, which can be used as a model to interpret the ecology and evolution of other fossils of pachycormiforms and stem teleosts. It also provides further context for the evolution of modern teleosts and how the extinction of pachycormiforms impacted modern marine diversity.